2011
DOI: 10.1159/000324822
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study of a New, Fully Automated System for Liquid-Based Cytology: The NovaPrep® Processor System

Abstract: Objective: To evaluate a fully automated system for liquid-based cytology (LBC): the NovaPrep® Processor System (NPS), which is based on the new concept of double decantation, versus conventional cytology (CC), the gold standard for cytology. Study Design: We performed a preliminary comparative study involving 1,129 female patients who underwent sampling for a Pap test; the sample was first smeared for CC and then, using the remaining specimen on the brush, for LBC with the NPS. The performances of CC and NPS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Dowie et al [13] said that nearly 1 min was saved after being accustomed to read the LBP. López-Cuervo et al [14] reported that the average reading time was 3.05 min in their last series of 197 cases using the NovaPrep® processor system, although they did not compare them with conventional smears. …”
Section: Discussionmentioning
confidence: 99%
“…Dowie et al [13] said that nearly 1 min was saved after being accustomed to read the LBP. López-Cuervo et al [14] reported that the average reading time was 3.05 min in their last series of 197 cases using the NovaPrep® processor system, although they did not compare them with conventional smears. …”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] Cervical carcinoma screening has been performed for more than 50 years by the conventional Pap smears, which has substantially reduced the incidence of cervical neoplasia, especially in developed countries by successfully identifying the asymptomatic women with preneoplastic lesions and early cervical neoplasia. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%